Optimalisasi dan Implementasi Media Sosial Sebagai Sarana Pemasaran UMKM Ayam Geprek Stroom - Auliya, Rahma; Putri Idawati, Amelia; Kusuma Ningrum, Salwa; Layla Wahyu I, Sri (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Ayam Geprek Stroom, a Micro, Small, and Medium Enterprise (MSME), is a culinary business located in Rembang Regency, Central Java. Based on a situational analysis, several challenges were identified among its partners, including limited business promotion, limited human resources, and suboptimal use of digital media as a marketing tool. This Business Work Lecture (KKU) program aims to increase the competitiveness and marketing reach of MSMEs by strengthening their visual identity and optimizing digital marketing. The implementation method was participatory, encompassing pre-surveys and permits, problem identification, strengthening the business's visual identity, enhancing digital marketing, monitoring and evaluation, program implementation, and closing. The program included menu catalog development, promotional banners and pamphlets, product photography enhancements for GrabFood and ShopeeFood, and the creation of social media accounts on Instagram and TikTok. The results of the program indicate that Ayam Geprek Stroom has more engaging and informative promotional media and has acquired digital marketing tools that can be used to reach a wider consumer base. The utilization of social media and online sales platforms is expected to increase business visibility, strengthen branding, and support sustainable sales growth.